2007
DOI: 10.1143/jjap.46.3039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anode Designs on Ion Emission Characteristics of a Plasma Focus Device

Abstract: A comparative study on the ion emission characteristics such as flux and energy, and their variation in angular positions and operating gas pressures has been carried out in a nitrogen-filling plasma focus device. Three different designs of cylindrical anode (central electrode) having hollow, solid and hemispherical tip have been tested for this study. The ion emission characteristics were investigated by employing three Faraday cups at various angular positions. The ion flux depends on the operating gas press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 29 publications
(42 reference statements)
2
16
0
Order By: Relevance
“…Such studies usually report the position of maxima or minima on the X or Y axes profiles22232425262728293031. As an example of 2D ion angular distribution profiles, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such studies usually report the position of maxima or minima on the X or Y axes profiles22232425262728293031. As an example of 2D ion angular distribution profiles, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, for all plasma-material interaction studies by means of different scale PFDs from PF-1000141819 to miniature PFDs20, the specimens are usually placed along the z-axis of the PFD chamber to be exposed to ions by applying several pinch shots21. Many exclusive studies have been performed on ion emission angular distribution profiles on X or Y axes of PFDs; some studies have reported maxima22232425 and some have shown minima262728293031, on the profiles, on or around the z-axis. Some theoretical models have also been developed to justify ion angular distribution profiles around the z axis222324293032333435.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, this type of pressure dependence of the ion beam flux is a commonly observed phenomenon in PF device. 35,36 While operating the PF device in nitrogen medium Mohanty et al 36 found more ion flux in between the pressure range of 0.3-0.5 Torr. The ion beam flux, in our case, is found to be more approximately at 0.3 Torr pressure as evident from Fig.…”
Section: -3mentioning
confidence: 99%
“…The emission of the polyenergetic ions is a general characteristic of the PF device. [35][36][37] However, the lowest and the highest energy ions may differ from the experiment to experiment and the detection methodology. Bostick et al observed the deuteron energy spectrum ranging from 300 keV to 9 MeV, 38 whereas Gardin et al measured the deuteron energy down to around 25 keV.…”
Section: -3mentioning
confidence: 99%